Ascension [videorecording (DVD)] - Kingdon, Jessica (Grasshopper Film, 2022)
"... explores the paradoxical pursuit of wealth and progress in China. Loosely structured around the distinct social and economic classes that divide the nation, this extraordinary documentary follows factory workers, middle class consumers and elites as they chase the elusive 'Chinese Dream.'"--Grasshopper Film website.